THE EFFECT OF EARLY MARRIAGE ON MATERNAL AND PERINATAL EMERGENCIES - Ratna, Wa Ode; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Early marriage usually occurs in adolescent under 19 years of age when the child is not physically, physiologically, or psychologically ready to assume the responsibilities of marriage and child-rearing. This. Data from the Kendari Women's Empowerment Service in 2022, the cases of early marriage increased to 36 cases from 13 cases in 2021. This research uses the literature review study search method via Google Scholar and PubMed. The populations in this study were mothers giving birth in their teens, namely early teens (10-14) years and middle teens (15-19) years. The results of the analysis show that the results of this literature review research show that there is a risk for teenage mothers giving birth. This is because the mother's young age means she is at greater risk of experiencing pregnancy complications because the reproductive organs are not the results of the research showed that there were informants who experienced one of the danger signs in pregnancy, namely a decrease in the baby's movements at 24 weeks of gestation and 32 weeks of gestation until the baby was born, causing death in the baby shortly after birth. Apart from that, there was one informant who experienced anemia which hurt the mother and experienced an abortion at 16 weeks of pregnancy. Therefore, outreach regarding the impact of early marriage needs to be carried out and also collaboration between community leaders and health workers very important to be done. Key words: Maternal; Perinatal, Early Marriage, Young age